The antimicrobial activity of honey from four species of Malaysian stingless bees, Trigona apicalis, Trigona carnifrons, Trigona itama and Trigona thoracica - Cheng, Yee Hong (2018)
Antimicrobial resistance (AMR) has become very important public health issue worldwide due to indiscriminate use of antimicrobials which eventually leads to failure of treatment such as for infected wounds. Honey from Apis bee and Meliponines (stingless honey bees) has been reported to have antimicrobial property. Recent development in stingless bee keeping in Malaysia has generated the interest to conduct this study aimed to determine the antimicrobial activity of fresh honey from four species of Malaysian stingless bees namely Trigona apicalis, Trigona carnifrons, Trigona itama and Trigona thoracica. A well diffusion assay was used to assess the antimicrobial activity of the four honeys against seven bacteria commonly found on infected wounds. The zone diameter of inhibition (ZDI) of the four honeys has been determined against Bacilus subtilis (0-29.3mm), Enterococci fecalis (0-21.5mm), Escherichia coli (0-31.9mm), Pasteurella multocida (24.3-40mm), Proteus mirabilis (0-21.3mm), Pseudomonas aeruginosa (7-21mm) and Staphylococcus aureus (10.6-30.7mm).The study findings revealed that all tested honeys showed antimicrobial activity. However, the statistical analysis indicated no significant difference. One of the reasons could be due to the similar type of flower nectar used by the bees. Nevertheless, the highest ZDI against all tested bacteria for Trigona thoracica honey found in this study warrants further investigation. Additionally, other characteristics such as the osmolarity, acidity, hydrogen peroxide and phenolic compound of the Malaysian stingless bee honey should also be investigated.